Irrigation scheduling using complex machine scheduling - Vries, T.T. de; Anwar, Arif A. (American Society of Civil Engineers, 2015)
Irrigation schedules are used in many irrigation schemes that operate on a rotational or arranged-demand basis. Determining these schedules is a complex problem, especially when done by hand. Operations research tools such as single machine scheduling are already used to schedule irrigation turns in systems where only one single user can irrigate simultaneously. This paper shows how multimachine scheduling can be used to determine arranged-demand schedules for systems where two or more users can irrigate at the same time. Two models are presented, as follows: (1) the simple multimachine scheduling model that establishes a schedule for systems where all outlets/user discharges are identical, and (2) the complex multimachine scheduling model that determines the schedule when flows to individual outlet/users are not necessarily identical.